Software-in-the-loop optimization of actuator and sensor placement for a smart piezoelectric funnel-shaped inlet of a magnetic resonance imaging tomograph. (15th January 2021) - Nestorović, Tamara; Hassw, Kevin; Oveisi, Atta
Graphical abstract: Highlights: Challenging problem of optimal piezoelectric actuator/sensor placement on curved surface solved. Global search based on H 2 and H ∞ employed provides controllability. Optimal placement verified through implementation of optimal LQR controller. Abstract: Performance of smart piezoelectric structures strongly depends on placement of integrated piezoelectric actuators and sensors, which may be implemented in the form of thin film layers on the structure surface or embedded within the structure. In both cases actuator and sensor placement plays an important role, since after applying they remain permanently integrated with structure. In this paper the optimization procedure for piezoelectric structures with curved surfaces is proposed based on the Software-in-the-Loop (SiL) methodology and balanced modal order reduction in combination with H 2 and H ∞ norms used in placement indices. The optimization procedure is a global one, since it seeks for optima across the entire domain of the structure. A special challenge is tackling the problem of curved surfaces. This problem is solved in this work for a funnel shaped structure – inlet of the magnetic resonance imaging tomopraph. A thorough mesh convergence study with respect to the eigenfrequency analysis is performed in order to obtain a reliable numeric finite element model for further optimization purposes. Material parameter optimization is performed as well. Based on placement indices optimal placement study is performed under consideration of several eigenmodes of interest. The optimization is performed for individual modes as well as for simultaneous consideration of multiple modes. The SiL approach with recurrent communication in each iteration of the optimization between the numerical simulation FE software and optimization tool designed in Python is implemented through the evaluation of the placement indices for candidate locations over the entire curved surface of the structure. Depending on support conditions, optimal locations of piezoelectric actuators and sensors are proposed.